2017
DOI: 10.3390/ijerph14080944
|View full text |Cite
|
Sign up to set email alerts
|

Biometeorological Assessment of Mortality Related to Extreme Temperatures in Helsinki Region, Finland, 1972–2014

Abstract: Climate change is expected to increase heat-related and decrease cold-related mortality. The extent of acclimatization of the population to gradually-changing thermal conditions is not well understood. We aimed to define the relationship between mortality and temperature extremes in different age groups in the Helsinki-Uusimaa hospital district in Southern Finland, and changes in sensitivity of the population to temperature extremes over the period of 1972–2014. Time series of mortality were made stationary wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…Daily air temperature was calculated as the mean from 12 high-quality meteorological stations operated by the Czech Hydrometeorological Institute, representing the spatial population distribution in the Czech Republic ( Figure 1 ), and used as a proxy variable of thermal conditions. While some studies have shown a theoretical advantage of indices combining multiple variables in order to assess human thermal comfort [ 69 ] as well as their better performance on mortality data [ 70 , 71 ], the differences between various temperature measures in evaluating heat’s impact on mortality are generally insignificant [ 36 , 72 , 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Daily air temperature was calculated as the mean from 12 high-quality meteorological stations operated by the Czech Hydrometeorological Institute, representing the spatial population distribution in the Czech Republic ( Figure 1 ), and used as a proxy variable of thermal conditions. While some studies have shown a theoretical advantage of indices combining multiple variables in order to assess human thermal comfort [ 69 ] as well as their better performance on mortality data [ 70 , 71 ], the differences between various temperature measures in evaluating heat’s impact on mortality are generally insignificant [ 36 , 72 , 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…in Australia, with decreases in outdoor labor the male heat mortality rate has fallen faster than the female rate (Coates et al 2014), and in the greater decreases that are seen with children mortality rates, with other studies showing slower decreases in the elderly mortality rate (Åström et al 2013b) or even a noticeable uptick (Ekamper et al 2009) indicative of changes in overall age structure. In studies confined to more recent decades, decreases in vulnerability have been most substantial in the oldest age groups (Ruuhela et al 2017, Sheridan and Dixon 2017, Bobb et al 2014, de'Donato et al 2015, although in others there was no consistent age-related differentiation Hagihara 2015, Ha andKim 2013).…”
Section: Causes Of Mortality and Morbiditymentioning
confidence: 97%
“…Rey et al (2007) Excess mortality was substantially lower than expected during 2006 heat wave in France, after the implementation of public health surveillance. Ruuhela et al (2017) In Finland, the sensitivity to heat stress has decreased from 1972-2014. Schifano et al (2012) A significant decrease in heat-related mortality in those 65 and older in Italy is observed in 2006-2010 following implementation of a national prevention plan.…”
Section: Overview Of the Approaches Usedmentioning
confidence: 99%
“…The population density of the study area is 1490 per km 2 . Although the study area is located in temperate zone with reasonably cool climate, UHI and heat waves during summer months are one of the key climatic and weather hazards in the area (Ruuhela et al 2017), and they have been emphasized in climate change adaptation plans (Helsinki Region Environmental Services Authority 2016a).…”
Section: Study Areamentioning
confidence: 99%